AHEAD Study: an observational study of the management of anticoagulated patients who suffer head injury. Issue 1 (13th January 2017) - Mason, Suzanne; Kuczawski, Maxine; Teare, M Dawn; Stevenson, Matt; Goodacre, Steve; Ramlakhan, Shammi; Morris, Francis; Rothwell, Joanne
Abstract : Objectives: Management of anticoagulated patients after head injury is unclear due to lack of robust evidence. This study aimed to determine the adverse outcome rate in these patients and identify risk factors associated with poor outcome. Design: Multicentre, observational study using routine patient records. Setting: 33 emergency departments in England and Scotland. Participants: 3566 adults (aged ≥16 years) who had suffered blunt head injury and were currently taking warfarin. Main outcome measures: Primary outcome measure was rate of adverse outcome defined as death or neurosurgery following initial injury, clinically significant CT scan finding or reattendance with related complication within 10 weeks of initial hospital attendance. Secondary objectives included identifying risk factors for adverse outcome using univariable and multivariable analyses. Results: Clinical data available for 3534/3566 patients (99.1%), median age 79 years; mean initial international normalised ratio (INR) 2.67 (SD 1.34); 81.2% Glasgow Coma Scale (GCS) 15: 59.8% received a CT scan with significant head injury-related finding in 5.4% (n=208); 0.5% underwent neurosurgery; 1.2% patients suffered a head injury-related death. Overall adverse outcome rate was 5.9% (95% CI 5.2% to 6.7%). Patients with GCS=15 and no associated symptoms had lowest risk of adverse outcome (risk 2.7%; 95% CI 2.1 to 3.6). Patients with GCS=15 multivariable analysis (using imputation) found risk of adverse outcome to increase when reporting at least one associated symptom: vomiting (relative risk (RR) 1.8; 95% CI 1.0 to 3.4), amnesia (RR 3.5; 95% CI 2.1 to 5.7), headache (RR 1.3; 95% CI 0.8 to 2.2), loss of consciousness (RR 1.75; 95% CI 1.0 to 3.0). INR measurement did not predict adverse outcome in patients with GCS=15 (RR 1.1; 95% CI 1.0 to 1.2). Conclusions: In alert warfarinised patients following head injury, the presence of symptoms is associated with greater risk of adverse outcome. Those with GCS=15 and no symptoms are a substantial group and have a low risk of adverse outcome. Trial registration number: NCT02461498.